Effects of conjugated linoleic acid on adipogenic genes regulation in chickens - Ramiah, Suriya Kumari (2015)
Modern commercial chickens exhibit excessive fat accumulation in the abdominal area. The major goals of the poultry industry are to increase the carcass yield and to reduce carcass fatness. Excessive fat deposition in chicken is detrimental for human consumption. Increasing the leanness of meat will improve the meat quality, and thus makes animals more valuable. Conjugated linoleic acid (CLA) consists of a complex mixture of geometrical (cis and trans) and positional isomers which consist of two major isomers; cis-9, trans-II CLA and trans-In, cis-I2 CLA. Animal studies have reported that dietary intake of CLA changes animal body composition by preventing obesity development. This study was performed with the hypothesis that CLA modified adipose tissue through alteration of the adipocyte genes. Therefore the general objective of current study was to evaluate the effects of CLA on lipid metabolism, cellular morphology and transcription of regulatory genes that were involved in adipogenesis of chickens. Cis-9, trans-l l CLA and trans-In, cis-TZ CLA isomers were evaluated individually for their effects on morphological changes, and adipogenic genes expressions on primary adipose tissue isolated from chicken Adipose tissue isolated from specific pathogen-free (SPF) chicken was cultured in induction media containing Dulbecco's Modified Eagle Medium (DMEM: HEM's (50:50); 1.5% bovine serum albumin; lOOnlM HEPES (4-(2-hydro>..)'ethyl)-1-piperazineethanesulfonic acid); 2mglmL collagenease type I, and 1% penicillin/streptomycin. The media were incorporated with two concentrations of both CLA isomers at 1.51% and 2.56% with a CONTROL group (without CLA isomers). After day 7, adipose tissues differentiation was monitored morphologically using ImageJ software, and adipogenic genes expressions were analyzed by real time polymerase chain reaction (PCR). It was observed that the efficacy of cis-9, trans-ll CLA isomer was more pronounced than trans-In, cis-12 CLA isomer in the in vitro study. Adipose tissue morphology data presented in this work revealed that the domination of cis-9, trans-l l isomer CLA effect was observed at higher concentration in the abdominal fat of broiler chickens. This was associated with a lower transcriptional level of peroxisome proliferator activated receptor gamma (PP AR y), and adipocyte protein 2 (aP2), together with lesser abdominal adipocyte volume and smaller amount of fat. The acyl-Coenzyme A binding domain containing 5 (ACBD 5), and lipoprotein lipase (LPL) were down-regulated by cis-9, trans-ll CLA isomer. The primary adipose tissue treated with trans-In, cis-I2 concentrations had no changes on the adipose cellularity and adipogenic genes. The influences of CLA supplementation on growth performance, fatty acid composition, lipid peroxidation, meat colour and plasma lipids in broiler chicken were investigated in this study. The CLA used in this study was of commercial feed grade (Lutrell® BSAF, SE, Ludwigshafen, Germany). A total of 180 broiler chickens were allocated to 3 dietary treatments (0,2.5 and 5% CLA), and given a standard broiler starter diet from 1 to 21 days, and finisher diet from 22 to 42 days. Body weight of chickens and feed intake were recorded weekly. After slaughter, the breast meat was aged at 4°C for 0, 3 and 6 days. The fatty acid composition was measured in the breast meat. The dietary CLA supplementation significantly (P<0.05) increased the content of CLA in chicken meat. The predominant CLA in meat from birds with supplemented diets was trans-It), cis-9. The proportion of monounsaturated (MUFA) fatty acid in meat decreased significantly (P<0.05) with increasing CLA supplementation. Dietary CLA also increased the thiobarbituric acid reactive substances (TBARS) values in breast meat. Conjugated linoleic acid feeding also resulted in the reduction of plasma total cholesterol, low-density protein, and the ratio of high-density protein, particularly among the 5% CLA fed-chickens. The effects of CLA on adipocytes morphology, fatty acid profile and PPARs associated genes were performed in CLA-fed chickens. The adipocyte morphology was analyzed using ImageJ software. It was also observed that the content of cis-9, trans-Ll CLA in abdominal fat tissue was higher than that of trans- 10, cis-12 CLA. The CLA feeding increased total saturated fatty acid and decreased the MUFA in concentration in broilers compared to the control group. Conjugated linoleic acid fed-chickens have lesser mean abdominal adipocyte volume and a smaller amount of fat because of reduced capacities to store fats. The influence on body composition appears to be dependent on PPAR a (alpha). Current study demonstrated that CLA down-regulated aP2 transcription, which was parallel to PPAR Y transcription in adipose tissue of broiler chickens. Adipocyte protein 2 (aP2) was regulated by PPAR Y as PP AR y is regarded as ,,master regulator" of adipocyte differentiation. The upregulation of LPL suggested that tins gene might play an independent role in regulation of adipogenesis in chicken model. The upregulation of ACBD 5 seems to be novel; therefore, more studies need to be done on this gene. However, LPL gene was not altered which indicates that the ex-pression of LPL occurs spontaneously at confluence and is independent. Therefore, tile current results supported the hypotheses that CLA modified adipose tissue through alteration of the adipocyte genes. It is evident that the CLA down-regulated PPAR y and aP2, which subsequently resulted in decreased adipocyte size, number and area of abdominal fat cells. The comparatively lower CLA content in poultry species could be mitigated through the use of feed and biotechnology approach to enhance CLA content. In conclusion, tile present results proved that CLA feeding is a practical strategy to reduce fat deposition in broiler chicken, while increasing its appeal to the general populace consuming chicken meat.